Stress coping and the early development of theory of mind and executive function : a study of preschoolers in Singapore. - Tham, Jayce Jinghui. (2011)
This study examined the relations between the executive function, theory of mind of 4-and 5-year old Singaporean preschoolers and 3 types of stress coping strategies, problem solving,social support and avoidance. Preschoolers (N = 20) were verbally interviewed about stress and coping. The Flexible Item Selection Task and the real and apparent emotion task was used as an executive function measure and theory of mind measure respectively. Family and social stressors were the major sources of stress and problem solving was used significantly more than social support or avoidance. The development of executive function was linked significantly with problem solving and social support. Theory of mind and preschoolers’ age were negatively correlated with avoidance strategies.